The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jtr.802
|View full text |Cite
|
Sign up to set email alerts
|

Deterrents to tourism development in Iran

Abstract: There are parts of the Middle East that can be regarded as being among the least preferred tourism destinations in the world. Research shows that travellers' perceptions of the region, as a whole, have been damaged and that, for some nations, the situation has gone from bad to worse. The combination of a hard-line attitude towards religion, oil and water shortages have led to the onset of war and confl ict, either among countries within the region, or have resulted in countries from within the region having co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 32 publications
(31 reference statements)
1
31
0
3
Order By: Relevance
“…The results also indicated that tourists should understand the image of their chosen destination through the visitation of the destination. Morakabati (2011) stressed that the image of a destination such as Iran is non-tourism specific, and closely linked to political propaganda and the country's relationship with other countries.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The results also indicated that tourists should understand the image of their chosen destination through the visitation of the destination. Morakabati (2011) stressed that the image of a destination such as Iran is non-tourism specific, and closely linked to political propaganda and the country's relationship with other countries.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the political propaganda, Iran is seen has a negative image in the world. In addition to its negative image in the world, unstable regional conditions and the absence of efficient advertising have also made a growth in tourism more difficult (Morakabati, 2011). According to statistics of the World Travel & Tourism Council (WTTC,), Iran currently ranks 92nd in the world in terms of tourism, while it is among the top 10 tourist countries in the world in terms of historical sites and natural resources (Iran's Cultural Heritage Handicraft and Tourism Organization, 2012).…”
Section: Iran and Its Image In The Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…The country ranks 10 th in hosting historical monuments and attractions (Morakabati, 2011), and is the 10 th country in the world with maximum ecotourism attractions (Armaghan, 2007). These rankings suggest that Iran involves high potentials in the field of tourism.…”
Section: 2tourism Industry and Tourism Infrastructure In Iranmentioning
confidence: 99%
“…Turizm alanında bir noktaya ulaşılabilme açısından güvenlikle ilgili genel imajın önemi çok fazladır. (Morakabati, 2011). Yapılacak tanıtım çalışmaları, harcanacak milyonlarca dolara rağmen "Gece yarısı ekspresi" veya "Borat" gibi filmlerin yarattığı imajı değiştirmek oldukça zordur.…”
Section: Gelişmekte Olan üLkelerde Turizmin Ekonomik Etkileri Ve Ortaunclassified